Nonaqueous electrolyte and nonaqueous electrolyte electricity storage element

By using high -content fluoride ring -shaped carbonate and fluoride chain solvents in non -hydrolysis, and the circular compounds of sulfur element are added, the capacity decreases and increases volume increase in silicon active substance electricity storage components The problem has achieved the effect of high capacity maintenance rate and less volume change.

CN119366027APending Publication Date: 2025-01-24GS YUASA INT LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380047104.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-16
Filing Date
2023-06-07
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the non-aqueous electrolyte power storage element using silicon-based active substances, problems such as decreasing discharge capacity and increasing volume caused by charge and discharge cycles are prone to occur.

Method used

By containing fluoride ring -shaped carbonate and fluoride chain solvents with more than 5 % percentage of more than 5 %, and an ring -shaped compound containing sulfur element is added to form high -quality membranes to inhibit gas generation and reduce volume changes.

Benefits of technology

In a non-aqueous electrolyte storage device using a silicon-based active material, it is possible to achieve both a high capacity retention rate and a small volume change after charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119366027A_ABST
    Figure CN119366027A_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte according to one aspect of the present invention is used in a non-aqueous electrolyte electricity storage element provided with a negative electrode having a silicon-based active material, and contains an electrolyte salt, a non-aqueous solvent containing a fluorinated cyclic carbonate and a fluorinated chain solvent, and a cyclic compound containing elemental sulfur, the content ratio of the fluorinated cyclic carbonate in the non-aqueous solvent is 5 vol% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte and a nonaqueous electrolyte storage element. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are mostly used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries are generally composed of a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are charged and discharged by transferring charge transport ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors have also been widely popularized.

[0003] It is known that there are non-aqueous electrolyte storage elements that use silicon-based active materials (active materials containing silicon elements) as negative electrode active materials (see Patent Documents 1 to 3). As silicon-based active materials, there are known simple silicon elements, silicon oxide, etc. Silicon-based active materials are expected to be promising negative electrode active materials because they have a larger discharge capacity than carbon-based active materials (carbon materials) such as graphite.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-053152

[0007] Patent Document 2: Japanese Patent Application Publication No. 2010-212228

[0008] Patent Document 3: Japanese Patent Application Publication No. 2004-356078 Summary of the invention

[0009] In the non-aqueous electrolyte storage element using silicon-based active materials, there is a disadvantage that the discharge capacity decreases due to the charge-discharge cycle is easy to occur. In contrast, according to the discovery of the present inventors, by making the non-aqueous electrolyte contain fluorinated cyclic carbonates such as fluoroethylene carbonate, there is a trend that the capacity retention rate after the charge-discharge cycle is improved. However, for the non-aqueous electrolyte storage element using silicon-based active materials, when the non-aqueous electrolyte containing fluorinated cyclic carbonate is used, the volume of the non-aqueous electrolyte storage element is greatly increased with the charge-discharge cycle. Other disadvantages. This is because the volume change caused by the silicon-based active material accompanying the charge and discharge is large, and the film formed on the surface of the silicon-based active material during the initial charge cannot fully follow the volume change of the silicon-based active material during the subsequent repeated charge and discharge. That is, due to the volume change of the silicon-based active material, cracks are generated in the film, so that the surface of the silicon-based active material is exposed and contacts with the fluorinated cyclic carbonate contained in the non-aqueous electrolyte, and the decomposition of the fluorinated cyclic carbonate occurs and produces gas, so the volume of the non-aqueous electrolyte storage element increases.

[0010] The present invention is based on the above-mentioned matters, and its purpose is to provide a non-aqueous electrolyte that can achieve both a high capacity retention rate and a small volume change after charge and discharge cycles in a non-aqueous electrolyte storage element having a negative electrode with a silicon-based active material, and a non-aqueous electrolyte storage element having such a non-aqueous electrolyte that can achieve both a high capacity retention rate and a small volume change after charge and discharge cycles.

[0011] The non-aqueous electrolyte involved in one aspect of the present invention is used in a non-aqueous electrolyte storage element having a negative electrode with a silicon-based active material, and contains: an electrolyte salt, a non-aqueous solvent containing a fluorinated cyclic carbonate and a fluorinated chain solvent, and a cyclic compound containing sulfur; the content ratio of the above-mentioned fluorinated cyclic carbonate in the above-mentioned non-aqueous solvent is 5 volume % or more.

[0012] A nonaqueous electrolyte power storage device according to another aspect of the present invention includes a negative electrode having a silicon-based active material and the nonaqueous electrolyte according to one aspect of the present invention.

[0013] According to one aspect of the present invention, there can be provided a non-aqueous electrolyte capable of achieving both a high capacity retention rate and a small volume change after charge and discharge cycles in a non-aqueous electrolyte storage element having a negative electrode with a silicon-based active material, and a non-aqueous electrolyte storage element having such a non-aqueous electrolyte capable of achieving both a high capacity retention rate and a small volume change after charge and discharge cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a perspective view showing an embodiment of a non-aqueous electrolyte electricity storage element.

[0015] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by combining a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION

[0016] First, the outline of the nonaqueous electrolyte and the nonaqueous electrolyte energy storage device disclosed in this specification will be described.

[0017] [1] A non-aqueous electrolyte according to one aspect of the present invention is used for a non-aqueous electrolyte storage element having a negative electrode having a silicon-based active material, and comprises: an electrolyte salt, a non-aqueous solvent comprising a fluorinated cyclic carbonate and a fluorinated chain solvent, and a cyclic compound comprising sulfur; the content ratio of the fluorinated cyclic carbonate in the non-aqueous solvent is 5% by volume or more.

[0018] The non-aqueous electrolyte described in [1] above can achieve both high capacity retention rate and small volume change after charge and discharge cycles in a non-aqueous electrolyte storage element having a negative electrode with a silicon-based active material. The reason is still uncertain, but it is speculated to be the following. In a non-aqueous electrolyte storage element using a silicon-based active material, the capacity retention rate after charge and discharge cycles is improved by making the non-aqueous solvent of the non-aqueous electrolyte contain 5% or more of fluorinated cyclic carbonate by volume. It is believed that this is due to the formation of a suitable film from fluorinated cyclic carbonates and the like on the surface of the silicon-based active material. However, when only fluorinated cyclic carbonates are used, the film formation reaction caused by the decomposition of fluorinated cyclic carbonates continues during the charge and discharge cycle, and gas is generated as a side reaction product, and the volume of the non-aqueous electrolyte storage element is greatly increased. In contrast, in the case of further adding a non-aqueous electrolyte containing a cyclic compound of sulfur element to a non-aqueous solvent containing a fluorinated cyclic carbonate and a fluorinated chain solvent, both the cyclic compound containing sulfur element and the fluorinated cyclic carbonate participate in the film formation, which can suppress the generation of gas as a side reaction product. On the other hand, since the film forming reaction involving both the fluorinated chain solvent and the cyclic compound containing sulfur element is not easy to proceed, the film forming reaction involving both the cyclic compound containing sulfur element and the fluorinated cyclic carbonate proceeds preferentially, and the generation of gas can be suppressed.

[0019] On the other hand, in the case of a non-aqueous electrolyte further adding a cyclic compound containing sulfur element to a non-aqueous solvent composed of a fluorinated cyclic carbonate and other solvents not containing a fluorinated chain solvent, a film formation reaction in which the cyclic compound containing sulfur element and other solvents participate will also be performed, consuming the cyclic compound containing sulfur element. As a result, the film formation reaction in which the cyclic compound containing sulfur element and the fluorinated cyclic carbonate participate will be hindered, and the decomposition reaction of the fluorinated cyclic carbonate will be performed, and gas generation cannot be fully suppressed. In addition, the film generated by the participation of the cyclic compound containing sulfur element and other solvents is not of high quality and cannot fully protect the surface of the silicon-based active material. Therefore, when a large amount of cyclic compounds containing sulfur element are contained in the non-aqueous solvent containing other solvents not containing a fluorinated chain solvent, a decrease in the capacity retention rate after the charge and discharge cycle is caused.

[0020] In addition, in the nonaqueous solvent that is only made of fluorinated cyclic carbonate, add the nonaqueous electrolyte of the cyclic compound that comprises sulfur element, because fluorinated cyclic carbonate exists in a large number, so can't fully suppress the decomposition of fluorinated cyclic carbonate.In addition, in the nonaqueous solvent that is only made of fluorinated cyclic carbonate, the nonaqueous electrolyte high viscosity is difficult to bring into play good charge-discharge performance sometimes.

[0021] Based on the above reasons, it is estimated that the nonaqueous electrolyte described in [1] can achieve both high capacity retention and small volume change after charge and discharge cycles in a nonaqueous electrolyte storage device having a negative electrode containing a silicon-based active material.

[0022] [2] In the non-aqueous electrolyte described in [1] above, the total content of the fluorinated cyclic carbonate and the fluorinated chain solvent in the non-aqueous solvent may be 60% by volume or more.

[0023] By using the nonaqueous electrolyte described in [2] above, the capacity retention rate of the nonaqueous electrolyte storage element after charge and discharge cycles can be further improved, and the volume change can be further reduced.

[0024] [3] In the non-aqueous electrolyte described in [1] or [2] above, the fluorinated chain solvent may be a fluorinated chain carbonate.

[0025] By using the nonaqueous electrolyte described in [3] above, the capacity retention rate of the nonaqueous electrolyte storage element after charge and discharge cycles can be further improved, and the volume change can be further reduced.

[0026] [4] In the non-aqueous electrolyte described in any one of [1] to [3] above, the concentration of the electrolyte salt may be 1.2 mol / dm 3 above.

[0027] By using the nonaqueous electrolyte described in [4] above, the volume change after the charge-discharge cycle of the nonaqueous electrolyte storage element can be further reduced. This reason is still uncertain, but it is believed that when the concentration of the electrolyte salt in the nonaqueous electrolyte is high, the fluorinated cyclic carbonate coordinated to the cation constituting the electrolyte salt becomes more and the free fluorinated cyclic carbonate is less. In such a case, it is speculated that the decomposition of the fluorinated cyclic carbonate and the gas generation brought therewith can be suppressed, and the volume change is reduced.

[0028] [5] In the nonaqueous electrolyte described in any one of [1] to [4] above, the cyclic compound containing elemental sulfur may have a cyclic sulfate ester structure or a sultone structure.

[0029] The present inventors have found that by using the nonaqueous electrolyte described in [5] above, as charge and discharge proceed, both the cyclic compound and the fluorinated cyclic carbonate participate in forming a particularly high-quality film, and the same film formation reaction occurs in the case of a compound having a cyclic sulfate structure and a compound having a sultone structure. Therefore, by using the nonaqueous electrolyte described in [5] above, the capacity retention rate of the nonaqueous electrolyte storage element after charge and discharge cycles can be further improved, and the volume change can be further reduced.

[0030] [6] In the non-aqueous electrolyte described in any one of [1] to [4] above, the cyclic compound containing sulfur element may have a sultone structure.

[0031] By using the nonaqueous electrolyte described in [6] above, a particularly high-quality film can be formed, thereby further suppressing the decomposition of the fluorinated cyclic carbonate and the resulting gas generation. Therefore, by using the nonaqueous electrolyte described in [6] above, the volume change of the nonaqueous electrolyte storage element after the charge and discharge cycle can be further reduced.

[0032] [7] In the nonaqueous electrolyte described in any one of [1] to [6] above, the cyclic compound containing sulfur element may have a carbon-carbon double bond.

[0033] By using the non-aqueous electrolyte described in [7] above, since the cyclic compound containing sulfur element has a carbon-carbon double bond, the LUMO (Lowest Unoccupied Molecular Orbital) of such a cyclic compound becomes low in calculation, and therefore it is easy to reduce and decompose at a high potential. Therefore, by using such a cyclic compound, a film formation reaction involving both the cyclic compound and the fluorinated cyclic carbonate is likely to occur before the fluorinated cyclic carbonate decomposes during charging, so the gas generation caused by the decomposition of the fluorinated cyclic carbonate can be suppressed. Therefore, by using the non-aqueous electrolyte described in [7] above, the volume change of the non-aqueous electrolyte storage element after the charge and discharge cycle can be further reduced.

[0034] [8] In the non-aqueous electrolyte described in any one of [1] to [5] above, the cyclic compound containing sulfur may be ethylene sulfate.

[0035] By using the nonaqueous electrolyte described in [8] above, a particularly high-quality film can be formed, thereby further suppressing the decomposition of the fluorinated cyclic carbonate and the resulting gas generation. Therefore, by using the nonaqueous electrolyte described in [8] above, the volume change of the nonaqueous electrolyte storage element after the charge and discharge cycle can be further reduced.

[0036] [9] The nonaqueous electrolyte according to any one of [1] to [8] can be used in a nonaqueous electrolyte storage device having a negative electrode including a silicon-based active material, wherein the silicon-based active material includes silicon oxide.

[0037] The nonaqueous electrolyte described in [9] above can achieve both high capacity retention and small volume change after charge and discharge cycles in a nonaqueous electrolyte storage device having a negative electrode having a silicon-based active material containing silicon oxide.

[0038]

[10] A nonaqueous electrolyte storage device according to another aspect of the present invention comprises: a negative electrode having a silicon-based active material; and the nonaqueous electrolyte according to any one of [1] to [9] above.

[0039] According to the nonaqueous electrolyte energy storage device described in

[10] above, the nonaqueous electrolyte energy storage device including the negative electrode having the silicon-based active material can achieve both high capacity retention rate and small volume change after charge and discharge cycles.

[0040]

[11] The nonaqueous electrolyte energy storage device described in

[10] above comprises: a negative electrode having a silicon-based active material containing silicon oxide, and the nonaqueous electrolyte described in any one of [1] to [9] above.

[0041] According to the nonaqueous electrolyte energy storage device described in

[11] above, the nonaqueous electrolyte energy storage device including a negative electrode having a silicon-based active material containing silicon oxide can achieve both high capacity retention and small volume change after charge and discharge cycles.

[0042] A nonaqueous electrolyte, a nonaqueous electrolyte storage element, a storage device, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments of the present invention are described in detail. It should be noted that the names of the components (components) used in each embodiment are sometimes different from the names of the components (components) used in the background art.

[0043] <Non-aqueous electrolyte>

[0044] The nonaqueous electrolyte involved in one embodiment of the present invention contains an electrolyte salt, a nonaqueous solvent and a cyclic compound containing sulfur. Usually, the electrolyte salt and the cyclic compound containing sulfur are dissolved in the nonaqueous solvent. The nonaqueous electrolyte is a nonaqueous electrolyte used in a nonaqueous electrolyte storage element having a negative electrode with a silicon-based active material. The nonaqueous electrolyte storage element having a negative electrode with a silicon-based active material is described in detail below.

[0045] (Electrolyte Salt)

[0046] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Salts, etc. Among these, lithium salts are preferred.

[0047] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, lithium oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalate borate (LiFOB), lithium bis(oxalate)difluorophosphate (LiFOP), lithium salts such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, LiC(SO2C2F5)3, etc. having halogenated hydrocarbon groups can be cited. Among these, inorganic lithium salts are preferred. From the viewpoints of oxidation resistance, good film formation, etc., the electrolyte salt preferably contains fluorine element. As an electrolyte salt, LiPF6 is more preferred. One or more of the electrolyte salts can be used.

[0048] The lower limit of the concentration of the electrolyte salt in the non-aqueous electrolyte can be 0.1 mol / dm at 20°C and 1 atmosphere. 3 , 0.3mol / dm 3 , 0.5mol / dm 3 Or 0.7 mol / dm 3, preferably 0.9 mol / dm 3 , more preferably 1.0 mol / dm 3 , more preferably 1.2 mol / dm 3 , and more preferably 1.4 mol / dm 3 When the concentration of the electrolyte salt in the non-aqueous electrolyte is above the above lower limit, the volume change of the non-aqueous electrolyte storage element after the charge and discharge cycle can be further reduced. The upper limit of the concentration of the electrolyte salt in the non-aqueous electrolyte is preferably 2.5 mol / dm at 20°C and 1 atmosphere. 3 , more preferably 2.0 mol / dm 3 , more preferably 1.7 mol / dm 3 , and more preferably 1.5 mol / dm 3 The concentration of the electrolyte salt in the nonaqueous electrolyte is greater than or equal to any of the lower limits described above and less than or equal to any of the upper limits described above.

[0049] (Non-aqueous solvent)

[0050] The non-aqueous solvent comprises a fluorinated cyclic carbonate and a fluorinated chain solvent. The fluorinated cyclic carbonate can form a good film on the surface of the silicon-based active material, and the oxidation resistance is also high. Therefore, the non-aqueous solvent can improve the capacity retention rate after the charge-discharge cycle in the non-aqueous electrolyte storage element with the negative electrode having the silicon-based active material by comprising the fluorinated cyclic carbonate. On the other hand, the fluorinated chain solvent is a solvent that is not easy to participate in the film formation reaction with the cyclic compound containing the sulfur element, and the oxidation resistance is also high. Therefore, the non-aqueous solvent, by comprising the fluorinated chain solvent, will not hinder the film formation reaction in which the cyclic compound containing the sulfur element and the fluorinated cyclic carbonate participate. In addition, the non-aqueous solvent, by comprising the fluorinated cyclic carbonate and the fluorinated chain solvent, makes the viscosity of the non-aqueous electrolyte appropriate, so that the non-aqueous electrolyte storage element can play a good charge-discharge performance.

[0051] Fluorinated cyclic carbonate is a kind of cyclic solvent, refers to a compound formed by a part or all of the hydrogen atoms possessed by cyclic carbonate being replaced by fluorine atoms. As fluorinated cyclic carbonate, fluorinated ethylene carbonates such as fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), fluorinated propylene carbonate, fluorinated butylene carbonate, etc. can be enumerated. Among these, preferably fluorinated ethylene carbonate, more preferably FEC. The oxidation resistance of FEC is high, and the capacity retention rate after the charge-discharge cycle in the nonaqueous electrolyte storage element can be fully improved. Fluorinated cyclic carbonate can use one or more than two kinds.

[0052] The lower limit of the containing ratio of the fluorinated cyclic carbonate in the non-aqueous solvent is 5 volume %, preferably 10 volume %, more preferably 15 volume %, further preferably 20 volume %, further preferably 25 volume %, particularly preferably 30 volume %.By making the containing ratio of the fluorinated cyclic carbonate be above the above lower limit, the capacity retention rate after the charge-discharge cycle in the non-aqueous electrolyte storage element can be improved.The upper limit of the containing ratio of the fluorinated cyclic carbonate in the non-aqueous solvent is preferably 80 volume %, more preferably 60 volume %, further preferably 50 volume %, further preferably 40 volume %, particularly preferably 35 volume %.By making the containing ratio of the fluorinated cyclic carbonate be below the above upper limit, the low viscosity of the non-aqueous electrolyte can be realized.The containing ratio of the fluorinated cyclic carbonate in the non-aqueous solvent can be above any lower limit and below any upper limit mentioned above.

[0053] Fluorinated chain solvent refers to a compound in which a part or all of the hydrogen atoms possessed by the chain solvent are replaced by fluorine atoms. As the fluorinated chain solvent, fluorinated chain hydrocarbons, fluorinated chain ethers, fluorinated chain esters, fluorinated chain carbonates, etc. can be enumerated, and fluorinated chain carbonates are particularly preferred. As the fluorinated chain solvent, it is also preferred to have a partial structure of CF3-CH2-O-. The fluorinated chain solvent can use one or more than two kinds.

[0054] Examples of the fluorinated chain carbonate include R a -O-CO-OR b (R a is a fluorinated alkyl group. b is an alkyl group or a fluorinated alkyl group. b Preferably, R a and R b The number of carbon atoms in each of 1 to 3 is preferably 1 to 3, more preferably 1 or 2.

[0055] As fluorinated linear carbonate, fluoromethyl methyl carbonate, fluoroethyl methyl carbonate, difluoroethyl methyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, methyl fluoropropyl carbonate, methyl difluoropropyl carbonate, methyl trifluoropropyl carbonate, methyl tetrafluoropropyl carbonate, methyl pentafluoropropyl carbonate, bis(trifluoropropyl) carbonate, bis(tetrafluoropropyl) carbonate, bis(pentafluoropropyl) carbonate etc. can be enumerated. Among these, 2,2,2-trifluoroethyl methyl carbonate (TFEMC) as trifluoroethyl methyl carbonate is preferred.

[0056] Examples of the fluorinated chain ester include methyl 3,3,3-trifluoropropionate (FMP), 2,2,2-trifluoroethyl acetate (FEA), methyl trifluoroacetate, ethyl trifluoroacetate, 2,2,2-trifluoroethyl trifluoroacetate, methyl 2-fluoropropionate, and ethyl 2-fluoropropionate.

[0057] Examples of the fluorinated ether include 1,1,2,2-tetrafluoro-2,2,2-trifluoroethyl ether (TFEE), 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3,3-pentafluoropropyl ether, and 1,1,2,2-tetrafluoropropyl-1,1,2,3,3,3-hexafluoropropyl ether.

[0058] The content of the fluorinated chain solvent in the non-aqueous solvent is preferably 20% to 95% by volume, more preferably 40% to 90% by volume, further preferably 50% to 85% by volume, further preferably 60% to 80% by volume, and particularly preferably 65% ​​to 75% by volume. By making the content of the fluorinated chain solvent within the above range, the capacity retention rate after charge and discharge cycles in the non-aqueous electrolyte storage element can be further improved, and the volume change can be further reduced.

[0059] The lower limit of the total containing ratio of the fluorinated cyclic carbonate in the nonaqueous solvent and the fluorinated chain solvent is preferably 60 volume %, more preferably 70 volume %, further preferably 80 volume %, further preferably 90 volume %, 95 volume % or 99 volume %.By making the total containing ratio of the fluorinated cyclic carbonate in the nonaqueous solvent and the fluorinated chain solvent be more than the above-mentioned lower limit, the capacity retention rate after the charge-discharge cycle in the nonaqueous electrolyte storage element can be further improved, and the volume change is further reduced.The upper limit of the total containing ratio of the fluorinated cyclic carbonate in the nonaqueous solvent and the fluorinated chain solvent can be 100 volume %.

[0060] The non-aqueous solvent may contain other non-aqueous solvents other than fluorinated cyclic carbonates and fluorinated chain solvents. As other non-aqueous solvents, non-fluorinated cyclic carbonates, non-fluorinated chain carbonates, esters other than fluorinated chain esters, ethers other than fluorinated chain ethers, etc. can be cited. As non-fluorinated cyclic carbonates, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, styrene carbonate, 1-phenyl vinylene carbonate, 1,2-diphenyl vinylene carbonate, etc. can be cited. As non-fluorinated chain carbonates, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, etc. can be cited.

[0061] The volume ratio of the cyclic solvent to the chain solvent in the nonaqueous solvent (cyclic solvent:chain solvent) is preferably in the range of, for example, 5:95 to 50:50.

[0062] The lower limit of the containing ratio of the cyclic carbonate (fluorinated cyclic carbonate and unfluorinated cyclic carbonate) in the cyclic solvent is preferably 60 volume %, more preferably 70 volume %, further preferably 80 volume %, further preferably 90 volume %, 95 volume % or 99 volume %.By making the containing ratio of the cyclic carbonate in the cyclic solvent be more than the above-mentioned lower limit, the capacity retention rate after the charge-discharge cycle in the nonaqueous electrolyte storage element can be further improved.The upper limit of the containing ratio of the cyclic carbonate in the cyclic solvent can be 100 volume %.

[0063] The lower limit of the containing ratio of the fluorinated cyclic carbonate in the cyclic carbonate is preferably 60 volume %, more preferably 70 volume %, further preferably 80 volume %, further preferably 90 volume %, 95 volume % or 99 volume %.By making the containing ratio of the fluorinated cyclic carbonate in the cyclic carbonate be more than the above-mentioned lower limit, the capacity retention rate after the charge-discharge cycle in the nonaqueous electrolyte storage element can be further improved.The upper limit of the containing ratio of the fluorinated cyclic carbonate in the cyclic carbonate can be 100 volume %.

[0064] The lower limit of the content ratio of the fluorinated chain solvent in the chain solvent is preferably 60 volume %, more preferably 70 volume %, further preferably 80 volume %, and further preferably 90 volume %, 95 volume % or 99 volume %. By making the content ratio of the fluorinated chain solvent in the chain solvent be above the above lower limit, the capacity retention rate after the charge and discharge cycle in the non-aqueous electrolyte storage element can be further improved, and the volume change can be further reduced. The upper limit of the content ratio of the fluorinated chain solvent in the chain solvent can be 100 volume %.

[0065] The lower limit of the containing ratio of the carbonate (the total of fluorinated cyclic carbonate, fluorinated linear carbonate and unfluorinated carbonate) in the nonaqueous solvent is preferably 60 volume %, more preferably 70 volume %, further preferably 80 volume %, further preferably 90 volume %, 95 volume % or 99 volume %.By making the containing ratio of the carbonate in the nonaqueous solvent be more than the above-mentioned lower limit, the capacity retention rate after the charge-discharge cycle in the nonaqueous electrolyte storage element can be further improved, further reducing volume change.The upper limit of the containing ratio of the carbonate in the nonaqueous solvent can be 100 volume %.

[0066] The lower limit of the total containing ratio of the fluorinated solvent (the total of fluorinated cyclic carbonate, fluorinated chain solvent and other fluorinated solvents) in the non-aqueous solvent is preferably 60 volume %, more preferably 70 volume %, further preferably 80 volume %, and further preferably 90 volume %, 95 volume % or 99 volume %. Fluorinated solvent refers to a solvent with fluorine element. By making the total containing ratio of the fluorinated solvent in the non-aqueous solvent be more than the above lower limit, the capacity retention rate after the charge and discharge cycle in the non-aqueous electrolyte storage element can be further improved, and the volume change is further reduced. The upper limit of the total containing ratio of the fluorinated solvent in the non-aqueous solvent can be 100 volume %.

[0067] (Cyclic compounds containing sulfur)

[0068] By including a cyclic compound containing sulfur element in a non-aqueous electrolyte together with a non-aqueous solvent containing a fluorinated cyclic carbonate and a fluorinated chain solvent, it is possible to achieve both a high capacity retention rate and a small volume change after charge and discharge cycles in a non-aqueous electrolyte storage element having a negative electrode with a silicon-based active material. The cyclic compound containing sulfur element is usually an organic compound. The cyclic compound containing sulfur element is preferably a compound having a heterocyclic structure containing sulfur element. As the cyclic compound containing sulfur element, compounds having a cyclic sulfate structure, a sultone structure, a cyclic sulfone structure, a cyclic sulfite structure, a cyclic sulfoxide structure, a cyclic thioether structure, etc. can be cited. One or more cyclic compounds containing sulfur element can be used.

[0069] The compound having a cyclic sulfate structure refers to a compound having a ring structure in which two carbon atoms are respectively bonded to an oxosulfonyloxy group (-OS(=O)2-O-). Specific examples of the compound having a cyclic sulfate structure include ethylene sulfate (ES), 1,3-propylene sulfate, 2,3-propylene sulfate, 4,5-pentylene sulfate, 4,4'-bis(2,2-dioxo-1,3,2-disulfonyl)sulfate, and 1,3-propylene sulfate. 4-Methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxo- Azothiophene, etc.

[0070] A compound having a sultone structure refers to a compound containing a ring structure in which two carbon atoms are respectively bonded to a sulfonyloxy group (-S(=O)2O-). A compound having a sultone structure is a type of cyclic sulfonate, and as a cyclic compound containing a sulfur element, it may be a cyclic sulfonate, preferably a compound having a sultone structure. Specific examples of compounds having a sultone structure include 1,3-propane sultone (PS), 1,4-butane sultone, 1,3-propene sultone (PRS), 1-methyl-1,3-propene sultone, 2-methyl-1,3-propene sultone, 3-methyl-1,3-propene sultone, 1,4-butene sultone, and the like. Specific examples of cyclic sulfonates other than compounds having a sultone structure include methylene disulfonate (MMDS) and the like.

[0071] The compound having a cyclic sulfone structure refers to a compound containing a ring structure in which two carbon atoms are respectively bonded to a sulfonyl group (-S(=O)2-). Specific examples of the compound having a cyclic sulfone structure include sulfolane, 3-methylsulfolane, 3-cyclobutene sulfone, 1,1-dioxythiophene, 3-methyl-2,5-dihydrothiophene-1,1-dioxide, and 3-cyclobutene sulfone-3-carboxylic acid methyl ester.

[0072] The compound having a cyclic sulfite structure refers to a compound having a ring structure in which two carbon atoms are respectively bonded to an oxosulfinyloxy group (-OS(=O)-O-). Specific examples of the compound having a cyclic sulfite structure include ethylene sulfite, 1,2-propylene glycol sulfite, trimethylene sulfite, 1,3-butylene glycol sulfite, and the like.

[0073] The compound having a cyclic sulfoxide structure refers to a compound having a ring structure in which two carbon atoms are respectively bonded to a sulfinyl group (-S(=O)-). Specific examples of the compound having a cyclic sulfoxide structure include tetramethylene sulfoxide and the like.

[0074] The compound having a cyclic sulfide structure refers to a compound containing a ring structure in which two carbon atoms are respectively bonded to divalent sulfur (-S-). Specific examples of the compound having a cyclic sulfide structure include tetrahydrothiophene, thiophene, cyclopentane sulfide, 1,3-cyclopentane disulfide, 5,6-dihydro-1,4-dithiene-2,3-dicarboxylic anhydride, and 3,4-thiophene dicarboxylic anhydride.

[0075] As the cyclic compound containing sulfur element, a compound having a ring structure containing a sulfonyl group (-S(=O)2-) is preferred. As such a compound, compounds having the above-mentioned cyclic sulfate structure, sultone structure, cyclic sulfone structure, etc. can be cited. As the cyclic compound containing sulfur element, a compound having a cyclic sulfate structure or a sultone structure is further preferred, a compound having a sultone structure is more preferred, and a compound having a carbon-carbon double bond and a sultone structure is further preferred. When the cyclic compound containing sulfur element is such a compound, the capacity retention rate after charge and discharge cycles in the non-aqueous electrolyte storage element can be further improved, and the volume change can be further reduced.

[0076] Among the compounds having a cyclic sulfate structure, there are compounds that exhibit excellent performance, such as ethylene sulfate (ES) described later. On the other hand, the compounds having a sultone structure are preferred in terms of structural stability or excellent solubility in non-aqueous solvents and easy handling compared to the compounds having a cyclic sulfate structure.

[0077] In addition, as a cyclic compound containing sulfur, a compound having a carbon-carbon double bond is also preferred, a compound having a carbon-carbon double bond in a heterocyclic structure containing sulfur is more preferred, and a compound having a carbon-carbon double bond in a sultone structure is further preferred. When the cyclic compound containing sulfur is such a compound, the capacity retention rate after the charge and discharge cycle in the non-aqueous electrolyte storage element can be further improved, and the volume change can be further reduced. As such a preferred compound, 1,3-propylene sultone (PRS), 1-methyl-1,3-propylene sultone, 2-methyl-1,3-propylene sultone, 3-methyl-1,3-propylene sultone, 1,4-butene sultone, etc., which are exemplified above, are cited, and 1,3-propylene sultone (PRS) is particularly preferred.

[0078] The cyclic compound containing sulfur element may be a compound composed of carbon element, hydrogen element, sulfur element and oxygen element. One or more cyclic compounds containing sulfur element may be used.

[0079] As the lower limit of the concentration of the cyclic compound containing sulfur element in the non-aqueous electrolyte, it is sometimes preferably 0.01 mass%, more preferably 0.1 mass%, further preferably 0.5 mass%, further preferably 1 mass%, further preferably 2 mass%, 3 mass% or 4 mass%. By making the concentration of the cyclic compound containing sulfur element above the above lower limit, the volume change after the charge and discharge cycle in the non-aqueous electrolyte storage element can be reduced. On the other hand, as the upper limit of the above concentration, it is sometimes preferably 12 mass%, more preferably 10 mass%, further preferably 8 mass%, further preferably 6 mass%, further preferably 4 mass%, 3 mass% or 2 mass%. By making the concentration of the cyclic compound containing sulfur element below the above upper limit, the capacity retention rate after the charge and discharge cycle in the non-aqueous electrolyte storage element can be further improved. The concentration of the cyclic compound containing sulfur element in the non-aqueous electrolyte can be above any of the above lower limits and below any of the above upper limits.

[0080] The non-aqueous electrolyte may contain other additives in addition to the electrolyte salt, the non-aqueous solvent and the cyclic compound containing the sulfur element. Examples of other additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; and amber. anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaric anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, diphenyl sulfide, thioanisole, diphenyl disulfide, perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, etc. These other additives may be used alone or in combination of two or more.

[0081] The content of other additives contained in the nonaqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass, relative to the overall mass of the nonaqueous electrolyte. By making the content of the additive within the above range, the capacity retention performance or cycle performance after high temperature storage can be improved, or the safety can be further improved.

[0082] In one embodiment of the present invention, the non-aqueous electrolyte may be a non-aqueous electrolyte. The non-aqueous electrolyte is, for example, a liquid non-aqueous electrolyte having fluidity at 20°C. The lower limit of the total content of the electrolyte salt, the non-aqueous solvent and the cyclic compound containing the sulfur element in the non-aqueous electrolyte may be 60% by mass, or 70% by mass, 80% by mass, 90% by mass or 95% by mass. The upper limit of the above total content may be 100% by mass. The non-aqueous electrolyte may further include a solid electrolyte, a polymer, etc. In one embodiment of the present invention, the non-aqueous electrolyte may be a gel electrolyte.

[0083] <Non-aqueous electrolyte energy storage device>

[0084] A nonaqueous electrolyte storage element (hereinafter also referred to as "storage element") according to one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator, a nonaqueous electrolyte, and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is usually a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator therebetween, or a wound type in which a positive electrode and a negative electrode are wound with a separator therebetween. The nonaqueous electrolyte exists in a state impregnated in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") is described.

[0085] (positive electrode)

[0086] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0087] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by measuring the volume resistivity of 10 -2 Ω·cm is used as a threshold value for determination. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.

[0088] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By making the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased, and the energy density of the non-aqueous electrolyte storage element can be increased.

[0089] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.

[0090] The positive electrode active material layer contains a positive electrode active material and may contain any components such as a conductive agent, a binder, a thickener, and a filler as required.

[0091] As the positive electrode active material, it can be appropriately selected from known positive electrode active materials. As the positive electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. As the positive electrode active material, for example, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur, etc. can be cited. As the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, for example, Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ)O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be mentioned. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be mentioned. Atoms or part of polyanions in these materials can be replaced by atoms or anions composed of other elements. The surfaces of these materials can be coated with other materials. In the positive electrode active material layer, one of these materials can be used alone, or two or more of them can be mixed and used.

[0092] As the positive electrode active material, lithium transition metal composite oxide is preferred, and lithium transition metal composite oxide having an α-NaFeO2 type crystal structure is more preferred. By using such a positive electrode active material, the discharge capacity of the nonaqueous electrolyte storage element can be increased.

[0093] The lithium transition metal composite oxide preferably contains nickel or manganese as the transition metal element, and more preferably contains both nickel and manganese. The lithium transition metal composite oxide may further contain other transition metal elements such as cobalt, typical metal elements such as aluminum, and the like.

[0094] As the lithium transition metal composite oxide having an α-NaFeO 2 type crystal structure, a compound represented by the following formula (1) is preferred.

[0095] Li 1+α Me 1-α O2···(1)

[0096] In the formula (1), Me is a metal element other than Li including Ni or Mn. 0≤α<1.

[0097] Me in formula (1) preferably contains Ni and Mn. It is also preferred that Me further contains Co. It is preferred that Me is substantially composed of two elements, Ni and Mn, or three elements, Ni, Mn and Co. Me may contain other metal elements such as Al.

[0098] In formula (1), the lower limit of the molar ratio (Ni / Me) of Ni to Me is preferably 0.1, more preferably 0.2, further preferably 0.3, and further preferably 0.4. On the other hand, the upper limit of the molar ratio (Ni / Me) is preferably 0.8, more preferably 0.7, and further preferably 0.6. The molar ratio (Ni / Me) may be above any of the lower limits and below any of the upper limits.

[0099] In formula (1), the lower limit of the molar ratio (Mn / Me) of Mn to Me is preferably 0.1, and more preferably 0.2. On the other hand, the upper limit of the molar ratio (Mn / Me) is preferably 0.7, more preferably 0.6, further preferably 0.5, and further preferably 0.4. The molar ratio (Mn / Me) may be greater than any of the lower limits described above and less than any of the upper limits described above.

[0100] In formula (1), the lower limit of the molar ratio (Co / Me) of Co to Me is preferably 0, more preferably 0.05, and further preferably 0.1. On the other hand, the upper limit of the molar ratio (Co / Me) is preferably 0.4, more preferably 0.3, and further preferably 0.2. The molar ratio (Co / Me) may be greater than any of the lower limits described above and less than any of the upper limits described above.

[0101] In formula (1), the molar ratio of Li to Me (Li / Me), that is, (1+α) / (1-α), may be 1.0 to 1.6, 1.0 to 1.2, or 1.0. α may be 0.

[0102] It should be noted that the composition ratio of the lithium transition metal composite oxide refers to the composition ratio when it is in a fully discharged state by the following method. First, the non-aqueous electrolyte storage element is charged at a constant current of 0.05C to the charging termination voltage during normal use, and becomes fully charged. After a 30-minute rest, it is discharged at a constant current of 0.05C to the lower limit voltage during normal use. Disassemble, remove the positive electrode, assemble a test battery with a metal lithium electrode as the counter electrode, and discharge at a constant current of 10mA per 1g of positive electrode mixture until the positive electrode potential becomes 2.0V vs.Li / Li + , adjust the positive electrode to a fully discharged state. Disassemble again and take out the positive electrode. Use dimethyl carbonate to thoroughly clean the attached non-aqueous electrolyte to the taken out positive electrode, and after drying at room temperature for 24 hours, collect the lithium transition metal composite oxide of the positive electrode active material. The collected lithium transition metal composite oxide is provided for measurement. The operations from the dismantling of the non-aqueous electrolyte storage element to the collection of the lithium transition metal composite oxide are carried out in an argon atmosphere with a dew point below -60°C. Here, normal use refers to the case where the non-aqueous electrolyte storage element is used under the charge and discharge conditions recommended or specified for the non-aqueous electrolyte storage element, and when a charger for the non-aqueous electrolyte storage element is prepared, it refers to the case where the non-aqueous electrolyte storage element is used using the charger.

[0103] The lower limit of the content of the lithium transition metal composite oxide relative to the total positive electrode active material in the positive electrode active material layer is preferably 50% by mass, more preferably 80% by mass, and further preferably 95% by mass. The content of the lithium transition metal composite oxide relative to the total positive electrode active material in the positive electrode active material layer may be 100% by mass.

[0104] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm to 20 μm. By making the average particle size of the positive electrode active material above the above lower limit, it is easy to manufacture or handle the positive electrode active material. By making the average particle size of the positive electrode active material below the above upper limit, the electronic conductivity of the positive electrode active material layer is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. "Average particle size" refers to the value of 50% of the volume-based cumulative distribution calculated according to JIS-Z-8819-2 (2001) by diluting the particles with a solvent according to JIS-Z-8825 (2013) and measuring the particle size distribution of the diluted solution by a laser diffraction / scattering method.

[0105] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill, or a sieve can be cited. During pulverization, wet pulverization in which an organic solvent such as water or hexane coexists can also be used. As a classification method, a sieve, a pneumatic classifier, etc. are used together with a dry method or a wet method as needed.

[0106] As the lower limit of the content of the positive electrode active material in the positive electrode active material layer, it is preferably 50% by mass, more preferably 70% by mass, further preferably 80% by mass, and further preferably 90% by mass. As the upper limit of the content of the positive electrode active material in the positive electrode active material layer, it is preferably 99.5% by mass, more preferably 99% by mass. By making the content of the positive electrode active material the above-mentioned range, the high energy density and manufacturability of the positive electrode active material layer can be obtained. The content of the positive electrode active material can be above any of the above-mentioned lower limits and below any of the above-mentioned upper limits.

[0107] As long as the conductive agent is a material with conductivity, there is no particular limitation. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be cited. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be cited. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be cited. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be cited. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be cited. As CNT, single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) can be cited. As the shape of the conductive agent, powder, fiber, etc. can be cited. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be composited and used. For example, a material composited with carbon black and CNT can be used.

[0108] The content of the conductive agent in the positive electrode active material layer is preferably 0.1% to 10% by mass, more preferably 0.2% to 5% by mass. When the content of the conductive agent is within the above range, the energy density of the nonaqueous electrolyte storage device can be increased.

[0109] As the binder, for example, there can be mentioned thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0110] The content of the binder in the positive electrode active material layer is preferably 0.4% by mass to 10% by mass, and more preferably 0.8% by mass to 5% by mass. When the content of the binder is within the above range, the positive electrode active material can be stably retained.

[0111] As thickeners, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be cited. In the case where the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. In one embodiment of the present invention, it is sometimes preferred that the positive electrode active material layer does not contain a thickener.

[0112] The filler is not particularly limited. As fillers, polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other materials from mineral resources or their man-made products, etc., can be cited. In one embodiment of the present invention, it is sometimes preferred that the positive electrode active material layer does not contain a filler.

[0113] The positive electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0114] (negative electrode)

[0115] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified in the above-mentioned positive electrode.

[0116] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel or their alloys, carbonaceous materials, etc. can be used. Among these, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.

[0117] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By making the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased, and the energy density of the non-aqueous electrolyte storage element can be increased.

[0118] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains any component such as a conductive agent, a binder, a thickener, and a filler as needed. The conductive agent, the binder, the thickener, the filler, and any component can be selected from the materials exemplified in the above-mentioned positive electrode.

[0119] The negative electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0120] The negative electrode active material includes a silicon-based active material. A silicon-based active material refers to an active material containing silicon. Examples of silicon-based active materials include simple silicon or compounds containing silicon. Examples of compounds containing silicon include silicon oxide (SiO x :0<x<2, preferably 0.8≤x≤1.2), silicon nitride, silicon carbide, metal silicon compounds, etc. As metal silicon compounds, compounds containing aluminum elements, tin elements, zinc elements, nickel elements, copper elements, titanium elements, vanadium elements, magnesium elements, etc. and silicon elements can be cited. In addition, as silicon-based active materials, composite materials such as SiO / Si / SiO2 composite materials can be used. Pre-doped substances can also be used as silicon-based active materials. That is, for example, the silicon-based active material can further contain lithium elements. The silicon-based active material can be used as one or a mixture of two or more. Among the silicon-based active materials, silicon oxide is preferred.

[0121] The surface of the silicon-based active material may be coated with a conductive material such as a carbonaceous material. By using such a silicon-based active material, the electronic conductivity of the negative electrode active material layer can be improved. When the silicon-based active material is in the form of particles coated with a conductive material, the mass ratio of the conductive material to the total amount of the silicon-based active material and the conductive material coating it is preferably 1 mass % to 10 mass %, and more preferably 2 mass % to 5 mass %.

[0122] The shape of the silicon-based active material is not particularly limited, but is preferably in the form of particles. The average particle size of the silicon-based active material can be, for example, 1 nm to 100 μm, or 50 nm to 50 μm. By making the average particle size of the silicon-based active material above the above lower limit, it is easy to manufacture or handle the silicon-based active material. By making the average particle size of the silicon-based active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain a powder with a specified particle size, a pulverizer or a classifier can be used. The pulverization method and the classification method can be selected, for example, from the methods exemplified in the above-mentioned positive electrode.

[0123] As the lower limit of the content of the silicon-based active material relative to the total negative electrode active material in the negative electrode active material layer, it is preferably 10% by mass, more preferably 50% by mass, and further preferably 70% by mass, 90% by mass, 95% by mass or 99% by mass. By making the content of the silicon-based active material above the above lower limit, the discharge capacity of the non-aqueous electrolyte storage element can be increased. On the other hand, when the content of the silicon-based active material relative to the total negative electrode active material is high, it is usually easy to cause cracking of the film and gas generation associated with the decomposition of the fluorinated cyclic carbonate, resulting in a decrease in discharge capacity and expansion of the negative electrode active material associated with the charge and discharge cycle. Therefore, one embodiment of the present invention is a non-aqueous electrolyte storage element in which the content of the silicon-based active material relative to the total negative electrode active material is above the above lower limit, and the advantages of high capacity retention rate and small volume change after charge and discharge cycles are more significant. The upper limit of the content of the silicon-based active material relative to the total negative electrode active material in the negative electrode active material layer can be 100% by mass.

[0124] The silicon-based active material preferably contains a large amount of silicon oxide. The lower limit of the content of silicon oxide in the silicon-based active material is preferably 60% by mass, more preferably 70% by mass, and further preferably 90% by mass, 95% by mass, or 99% by mass. By making the content of silicon oxide in the silicon-based active material above the above lower limit, the discharge capacity of the non-aqueous electrolyte storage element can be increased.

[0125] The negative electrode active material may include other negative electrode active materials in addition to the silicon-based active material. Examples of other negative electrode active materials include metals or semimetals such as Sn; metal oxides or semimetal oxides such as Ti oxide and Sn oxide; Li4Ti5O 12 、LiTiO 2、 Titanium-containing oxides such as TiNb2O7; polyphosphate compounds; silicon carbide; carbon materials such as graphite, non-graphite carbon (graphitizable carbon or non-graphitizable carbon), etc.

[0126] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% to 99% by mass, more preferably 80% to 98% by mass, and further preferably 85% to 95% by mass. By setting the content of the negative electrode active material to the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0127] As the conductive agent used in the negative electrode active material layer, the conductive agent is preferably a fibrous conductive agent, as exemplified in the positive electrode. As the fibrous conductive agent, fibrous carbon materials such as carbon nanotubes (CNTs) and pitch-based carbon fibers can be cited, among which CNTs are preferred, and SWCNTs are more preferred. By using such a conductive agent, good electronic conductivity can be fully exerted with a small amount.

[0128] The content of the conductive agent in the negative electrode active material layer is preferably 0.1 mass % to 10 mass %. The lower limit may be 0.2 mass % or 0.3 mass %. On the other hand, the upper limit is sometimes preferably 5 mass %, more preferably 1 mass % or 0.5 mass %. For example, as described above, by using a fibrous conductive agent, good electronic conductivity can be fully exerted with a small amount.

[0129] The binder used in the negative electrode active material layer is the same as the binder exemplified in the positive electrode, and among them, styrene butadiene rubber (SBR) is preferred.

[0130] The content of the binder in the negative electrode active material layer is preferably 1 to 30 mass %, more preferably 4 to 15 mass %, and further preferably 6 to 12 mass %. When the content of the binder is within the above range, the negative electrode active material can be stably retained.

[0131] The thickener used in the negative electrode active material layer is the same as the thickener exemplified for the positive electrode. The negative electrode active material layer preferably contains a thickener.

[0132] The content of the thickener in the negative electrode active material layer is preferably 0.3% by mass to 5% by mass, and more preferably 0.6% by mass to 3% by mass.

[0133] The filler used in the negative electrode active material layer is the same as the filler exemplified in the positive electrode. In one embodiment of the present invention, it is sometimes preferred that the negative electrode active material layer does not contain a filler.

[0134] (Isolator)

[0135] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and a binder formed on one or both surfaces of the substrate layer, and the like can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, and the like can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of insulation function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides and aromatic polyamides are preferred. As the substrate layer of the separator, a material obtained by compounding these resins can be used.

[0136] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is increased from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as organosilicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products. As inorganic compounds, these substances can be used alone, or two or more can be mixed or composited for use. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.

[0137] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a value based on volume, and refers to a value measured by a mercury porosimeter.

[0138] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As the polymer, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. When a polymer gel is used, there is an effect of suppressing leakage. As a separator, a porous resin film or non-woven fabric as described above can be used together with a polymer gel.

[0139] (Non-aqueous electrolyte)

[0140] The nonaqueous electrolyte included in the nonaqueous electrolyte storage element according to one embodiment of the present invention is the nonaqueous electrolyte according to one embodiment of the present invention described above.

[0141] (Shape, etc.)

[0142] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.

[0143] Figure 11 shows a non-aqueous electrolyte storage element 1 as an example of a square battery. It should be noted that this figure is a perspective view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.

[0144] <Electricity storage device>

[0145] The non-aqueous electrolyte storage element of the present embodiment can be mounted as a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements in an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) and other automotive power sources, a power source for electronic devices such as a personal computer and a communication terminal, or a power source for power storage, etc. In this case, the technology of the present invention can be applied to at least one non-aqueous electrolyte storage element included in the storage unit.

[0146] Figure 2 2 shows an example of an electric storage device 30 obtained by further combining an electric storage unit 20 formed by combining two or more electrically connected non-aqueous electrolyte storage elements 1. The electric storage device 30 may include a bus bar (not shown) that electrically connects the two or more non-aqueous electrolyte storage elements 1, a bus bar (not shown) that electrically connects the two or more electric storage units 20, and the like. The electric storage unit 20 or the electric storage device 30 may include a state monitoring device (not shown) that monitors the state of one or more non-aqueous electrolyte storage elements.

[0147] <Method for producing non-aqueous electrolyte storage element>

[0148] The manufacturing method of the non-aqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method, for example, comprises: a step of preparing an electrode body, a step of preparing a non-aqueous electrolyte, and a step of accommodating the electrode body and the non-aqueous electrolyte in a container. The step of preparing the electrode body comprises: a step of preparing a positive electrode and a negative electrode, and a step of forming an electrode body by stacking or winding the positive electrode and the negative electrode through a separator.

[0149] The step of storing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when the non-aqueous electrolyte is a non-aqueous electrolyte solution, the non-aqueous electrolyte solution can be injected from an injection port formed in the container and then the injection port can be sealed.

[0150] <Other embodiments>

[0151] It should be noted that the nonaqueous electrolyte and nonaqueous electrolyte storage element of the present invention are not limited to the above-mentioned embodiments, and various changes can be made without departing from the scope of the main purpose of the present invention. For example, the structure of other embodiments can be added to the structure of a certain embodiment, and in addition, a part of the structure of a certain embodiment can be replaced with the structure of other embodiments or known technology. In addition, a part of the structure of a certain embodiment can be deleted. In addition, known technology can be added to the structure of a certain embodiment.

[0152] In the above embodiment, the non-aqueous electrolyte storage element is used as a rechargeable non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) for example, but the type, shape, size, capacity, etc. of the non-aqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors, or lithium ion capacitors.

[0153] In the above embodiment, the electrode body is described as a stacked positive electrode and a negative electrode with a separator interposed therebetween, but the electrode body may not have a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state where a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode.

[0154] Example

[0155] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the following examples.

[0156] [Example 1]

[0157] (Production of positive electrode)

[0158] As the positive electrode active material, LiNi 0.5 Co 0.2 Mn 0.3 Lithium transition metal composite oxide represented by O2.

[0159] A positive electrode mixture paste is prepared, which contains the positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder at a mass ratio of 93:4:3 (solid content conversion), and contains N-methylpyrrolidone (NMP) as a dispersion medium. The positive electrode mixture paste is applied on an aluminum foil as a positive electrode substrate, and pressed after drying to produce a positive electrode having a positive electrode active material layer arranged on the positive electrode substrate.

[0160] (Production of negative electrode)

[0161] As the negative electrode active material, silicon oxide (SiO) doped with lithium in advance was used.

[0162] A negative electrode mixture paste is prepared, which contains the above-mentioned negative electrode active material, single-walled carbon nanotubes (SWCNT) as a conductive agent, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener at a mass ratio of 89.7:0.3:8.8:1.2 (solid content conversion), and contains water as a dispersion medium. The above-mentioned negative electrode mixture paste is applied on a copper foil as a negative electrode substrate and dried to prepare a negative electrode having a negative electrode active material layer arranged on the negative electrode substrate.

[0163] (Preparation of non-aqueous electrolyte)

[0164] By making LiPF6 at 1.0 mol / dm 3 The solution was prepared by dissolving fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethylmethyl carbonate (TFEMC) in a mixed solvent at a volume ratio of 30:70. 1,3-Propene sultone (PRS), a cyclic compound containing sulfur element, was further dissolved in the above solution at a concentration of 2.0 mass % to prepare a non-aqueous electrolyte.

[0165] (Fabrication of non-aqueous electrolyte storage element)

[0166] The positive electrode and the negative electrode are wound in an overlapping state through a polyolefin microporous film as a separator to produce an electrode body. The electrode body is housed in a container made of a metal-resin composite film, the non-aqueous electrolyte is injected into the container, and the container is sealed by heat melting to obtain the non-aqueous electrolyte storage element of Example 1.

[0167] [Examples 2 to 7 and Comparative Examples 1 to 5]

[0168] The concentration of the electrolyte salt (LiPF6) in the non-aqueous electrolyte, the composition (type and volume ratio) of the non-aqueous solvent, and the concentration of the cyclic compound (PRS) containing the sulfur element were set as shown in Tables 1 and 2. The same procedure as in Example 1 was followed to obtain non-aqueous electrolyte storage elements of Examples 2 to 7 and Comparative Examples 1 to 5. It should be noted that Example 1 is described in both Tables 1 and 2. In addition, "EMC" in Table 1 is ethyl methyl carbonate.

[0169] Each of the obtained nonaqueous electrolyte storage elements was sandwiched between two stainless steel plates and the four corners thereof were clamped to be in a compressed state, and the following capacity confirmation test and charge-discharge cycle test were performed.

[0170] (Capacity confirmation test)

[0171] A capacity confirmation test was performed on each nonaqueous electrolyte storage element in an environment of 25° C. according to the following procedure.

[0172] The battery was charged at a constant current and constant voltage with a charging current of 0.2C and a charging end voltage of 4.4V. The charging end condition was that the charging current reached 0.05C. After that, a rest period of 10 minutes was set. After that, the battery was discharged at a constant current with a discharge current of 0.1C and a discharge end voltage of 2.5V. The discharge capacity at this time was set as the "initial discharge capacity".

[0173] At this time, the current of 0.1C can be estimated based on the positive electrode capacity, negative electrode capacity, design of the non-aqueous electrolyte storage element, etc. In the capacity confirmation test of the non-aqueous electrolyte storage element, when constant current discharge is performed with a current of 0.1C, the effectiveness of the current of 0.1C is confirmed by setting the discharge time to approximately 10 hours.

[0174] (Charge and discharge cycle test)

[0175] Each non-aqueous electrolyte storage element after the above-mentioned capacity confirmation test is subjected to a charge and discharge cycle test in an environment of 25°C according to the following steps. Constant current and constant voltage charging is performed with the charging current recorded in Tables 1 and 2 and a charge termination voltage of 4.4V. The charge termination condition is the moment when the charging current decays to 0.05C. Thereafter, constant current discharge is performed with the discharge current recorded in Tables 1 and 2 and a discharge termination voltage of 2.5V. A rest period of 10 minutes is set after charging and after discharging, respectively. The charge and discharge process is set to 1 cycle, and a charge and discharge cycle test of 300 cycles is performed.

[0176] (Capacity maintenance rate)

[0177] After the above-mentioned charge-discharge cycle test, the above-mentioned capacity confirmation test is performed. The discharge capacity at this time is referred to as the "discharge capacity after the charge-discharge cycle test". The percentage of the discharge capacity after the charge-discharge cycle test relative to the initial (before the charge-discharge cycle test) discharge capacity is calculated as the capacity retention rate. The results are shown in Tables 1 and 2.

[0178] (Volume Change)

[0179] In the stage after 100 cycles and the stage after 300 cycles in the above-mentioned charge and discharge cycle test, the volume of each non-aqueous electrolyte storage element was measured by the Archimedean method. The difference between the volume after 100 cycles and the volume after 300 cycles was obtained as the volume change. The non-aqueous electrolyte storage element of Comparative Example 5 was not measured for volume change. The results are shown in Tables 1 and 2. It should be noted that the increase is expressed as a positive value and the decrease is expressed as a negative value.

[0180]

[0181]

[0182] As shown in Table 1, the capacity retention rate of the nonaqueous electrolyte storage element of Comparative Example 1 using a nonaqueous electrolyte containing FEC as a fluorinated cyclic carbonate and TFEMC as a fluorinated chain solvent but not containing PRS as a cyclic compound containing sulfur element is high, but the volume change is large. The volume change of the nonaqueous electrolyte storage element of Comparative Example 2 using a nonaqueous electrolyte containing no fluorinated chain solvent and no cyclic compound containing sulfur element is also large. The volume change of the nonaqueous electrolyte storage element of Comparative Examples 3 and 4 using a nonaqueous electrolyte containing a cyclic compound containing sulfur element added to the nonaqueous electrolyte of Comparative Example 2 is also large. The capacity retention rate of the nonaqueous electrolyte storage element of Comparative Example 5 using a nonaqueous electrolyte containing a cyclic compound containing sulfur element further added to the nonaqueous electrolyte of Comparative Examples 3 and 4 is greatly reduced.

[0183] Compared with these comparative examples, each nonaqueous electrolyte storage element of Examples 1 to 4 using a nonaqueous electrolyte containing FEC as a fluorinated cyclic carbonate and TFEMC as a fluorinated chain solvent and further containing PRS as a cyclic compound containing sulfur element has a high capacity retention rate and a small volume change. In addition, through the comparison of Examples 1 to 3, the comparison of Example 1 and Example 4, etc., it can be seen that by increasing the concentration of the cyclic compound containing sulfur element and increasing the concentration of the electrolyte salt, there is a trend that the volume change becomes smaller.

[0184] It should be noted that in Comparative Example 3 and Comparative Example 4, the nonaqueous electrolyte storage element is the same, and the charging current and the discharging current in the charge-discharge cycle test are different. In the results of Comparative Example 3 and Comparative Example 4, there is not much difference in the capacity retention rate and the volume change. That is, in the embodiment and the comparative example in Table 1, although the charging current and the discharging current in the charge-discharge cycle test are different, it is considered that the difference has little effect on the result.

[0185] In addition, as shown in Table 2, it is known that by improving the containing ratio of FEC as fluorinated cyclic carbonate, there is a trend that the capacity retention rate improves and the volume change becomes larger. It is known that fluorinated cyclic carbonate is a non-aqueous solvent required for the capacity retention rate in the charge-discharge cycle but on the other hand it is a non-aqueous solvent that can produce other topics such as volume change becoming larger.

[0186] [Examples 8 to 9]

[0187] The non-aqueous electrolyte storage elements of Examples 8 to 9 were obtained in the same manner as in Example 1 except that the concentration of the electrolyte salt (LiPF6) in the non-aqueous electrolyte was set as shown in Table 3. Using these non-aqueous electrolyte storage elements, the above-mentioned evaluation tests were performed under the same conditions as in Example 1. The results are shown in Table 3 together with Examples 1 and 4.

[0188]

[0189] As shown in Table 3, it can be seen that by setting the electrolyte salt concentration to 1.2 mol / dm 3 As described above, the volume change of the nonaqueous electrolyte electricity storage element after the charge and discharge cycle can be further reduced.

[0190] [Example 10]

[0191] The nonaqueous electrolyte storage element of Example 10 was obtained in the same manner as in Example 4 except that the mass of the nonaqueous electrolyte injected into the container was the same as that in Comparative Example 4. Using this nonaqueous electrolyte storage element, the above-mentioned evaluation tests were performed under the same conditions as in Example 1. The results are shown in Table 4 together with Comparative Example 4 and Example 4. It should be noted that the volume ratio and mass ratio of the injection amount of the nonaqueous electrolyte injected into the container in each Example and Comparative Example are respectively expressed as relative values ​​based on Comparative Example 4.

[0192]

[0193] As shown in Table 4, it can be seen that in Example 10, in which the mass of the non-aqueous electrolyte injected into the container is reduced to the same amount as that of Comparative Example 4 compared to Example 4, the volume change of the non-aqueous electrolyte storage element after the charge and discharge cycle can be fully suppressed compared to Comparative Example 4 which does not contain a fluorinated chain solvent.

[0194] [Example 11]

[0195] By making LiPF6 at 1.6 mol / dm 3 A solution is prepared by dissolving fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl acetate (FEA) in a mixed solvent at a volume ratio of 30:70. 1,3-Propene sultone (PRS), a cyclic compound containing sulfur element, is dissolved in the above solution at a concentration of 2.0 mass % to prepare a non-aqueous electrolyte. Using the above non-aqueous electrolyte, the same procedure as in Example 10 is performed except that the non-aqueous electrolyte storage element of Example 11 is obtained.

[0196] [Example 12]

[0197] By making LiPF6 at 1.6 mol / dm 3Solution A was prepared by dissolving fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl methyl carbonate (TFEMC) in a mixed solvent in a volume ratio of 30:70. Solution B was prepared by dissolving 1,3-propene sultone (PRS), a cyclic compound containing sulfur element, in the above solution A at a concentration of 2.0 mass %. 1,1,2,2-tetrafluoro-2,2,2-trifluoroethyl ether (TFEE) was further added to the above solution B at a concentration of 10 mass % to prepare a non-aqueous electrolyte. Using the above non-aqueous electrolyte, the same procedure as in Example 10 was performed except that the non-aqueous electrolyte was used to obtain the non-aqueous electrolyte storage element of Example 12.

[0198] Using these nonaqueous electrolyte storage devices, the above-mentioned evaluation tests were carried out under the same conditions as in Example 1. The results are shown in Table 5 together with those of Example 10.

[0199]

[0200] As shown in Table 5, it can be seen that the fluorinated chain solvent may be a fluorinated chain ester or a fluorinated ether, but preferably contains a fluorinated chain carbonate.

[0201] [Example 13]

[0202] A nonaqueous electrolyte was prepared in the same manner as in Example 1 except that 1,3-propane sultone (PS) was used instead of 1,3-propylene sultone (PRS). A nonaqueous electrolyte storage element of Example 13 was obtained in the same manner as in Example 10 except that the nonaqueous electrolyte was used.

[0203] [Example 14]

[0204] A nonaqueous electrolyte was prepared in the same manner as in Example 1 except that ethylene sulfate (ES) was used instead of 1,3-propene sultone (PRS). A nonaqueous electrolyte storage element of Example 14 was obtained in the same manner as in Example 10 except that the nonaqueous electrolyte was used.

[0205] [Example 15]

[0206] A nonaqueous electrolyte was prepared in the same manner as in Example 1 except that methylene methanedisulfonate (MMDS) was used instead of 1,3-propene sultone (PRS). A nonaqueous electrolyte storage element of Example 15 was obtained in the same manner as in Example 10 except that the nonaqueous electrolyte was used.

[0207] The above-mentioned evaluation tests were performed using the nonaqueous electrolyte storage devices of Examples 13 to 15 under the same conditions as in Example 1. The results are shown in Table 6 together with those of Example 10.

[0208]

[0209] As shown in Table 6, it can be seen from the comparison of the results of Example 10 and Example 13 that the volume change of the non-aqueous electrolyte storage element after the charge and discharge cycle can be further reduced by making the cyclic compound containing sulfur a compound having a carbon-carbon double bond. In addition, according to the results of Example 14, it can be seen that the cyclic compound containing sulfur is also preferably ethylene sulfate (ES).

[0210] Industrial Applicability

[0211] The present invention is applicable to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.

[0212] Explanation of symbols

[0213] 1 Non-aqueous electrolyte storage element

[0214] 2 Electrode body

[0215] 3 Container

[0216] 4 Positive terminal

[0217] 41 positive lead

[0218] 5 Negative terminal

[0219] 51 negative lead

[0220] 20 Storage Unit

[0221] 30Electrical storage device

Claims

1. A non-aqueous electrolyte for use in a non-aqueous electrolyte storage element having a negative electrode having a silicon-based active material, The non-aqueous electrolyte contains: Electrolyte salts, A non-aqueous solvent comprising a fluorinated cyclic carbonate and a fluorinated chain solvent, and Cyclic compounds containing the element sulfur, The content ratio of the fluorinated cyclic carbonate in the non-aqueous solvent is 5% by volume or more.

2. The nonaqueous electrolyte according to claim 1, wherein The total content of the fluorinated cyclic carbonate and the fluorinated chain solvent in the non-aqueous solvent is 60% by volume or more.

3. The nonaqueous electrolyte according to claim 1 or 2, wherein The fluorinated chain solvent is a fluorinated chain carbonate.

4. The nonaqueous electrolyte according to claim 1 or 2, wherein The concentration of the electrolyte salt is 1.2 mol / dm 3 above.

5. The nonaqueous electrolyte according to claim 1 or 2, wherein The cyclic compound containing sulfur element has a cyclic sulfate ester structure or a sultone structure.

6. The nonaqueous electrolyte according to claim 1 or 2, wherein The cyclic compound containing sulfur element has a sultone structure.

7. The nonaqueous electrolyte according to claim 1 or 2, wherein The cyclic compound containing sulfur element has a carbon-carbon double bond.

8. The nonaqueous electrolyte according to claim 1 or 2, wherein The cyclic compound containing sulfur element is ethylene sulfate.

9. The nonaqueous electrolyte according to claim 1 or 2, used for a nonaqueous electrolyte storage element having a negative electrode having a silicon-based active material, wherein The silicon-based active material includes silicon oxide.

10. A non-aqueous electrolyte storage element comprising: A negative electrode having a silicon-based active material, and The non-aqueous electrolyte according to claim 1 or 2.

11. The nonaqueous electrolyte storage element according to claim 10, wherein The silicon-based active material includes silicon oxide.

Citation Information

Patent Citations

  • Composite particle and manufacturing method therefor as well as negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte battery using the negative electrode

    JP2004356078A

  • Nonaqueous secondary battery

    JP2010212228A

  • Nonaqueous electrolytic secondary battery

    JP2015053152A